∫(0,+∞) e^-xdx=1。
解答過程如下:
∫ e^(-x)dx
=∫ -e^(-x)d(-x)
= -e^(-x) +C,C為常數。
所以
∫(0,+∞) e^(-x)dx
= -e^(-x) ,代入上下限+∞和0
= -e^(-∞) +e^0
顯然e^(-∞)=0,而e^0=1
= 1
擴充套件資料:
分部積分:
(uv)"=u"v+uv"
得:u"v=(uv)"-uv"
兩邊積分得:∫ u"v dx=∫ (uv)" dx - ∫ uv" dx
即:∫ u"v dx = uv - ∫ uv" d,這就是分部積分公式
也可簡寫為:∫ v du = uv - ∫ u dv
常用積分公式:
1)∫0dx=c
2)∫x^udx=(x^(u+1))/(u+1)+c
3)∫1/xdx=ln|x|+c
4)∫a^xdx=(a^x)/lna+c
5)∫e^xdx=e^x+c
6)∫sinxdx=-cosx+c
7)∫cosxdx=sinx+c
8)∫1/(cosx)^2dx=tanx+c
9)∫1/(sinx)^2dx=-cotx+c
10)∫1/√(1-x^2) dx=arcsinx+c
∫(0,+∞) e^-xdx=1。
解答過程如下:
∫ e^(-x)dx
=∫ -e^(-x)d(-x)
= -e^(-x) +C,C為常數。
所以
∫(0,+∞) e^(-x)dx
= -e^(-x) ,代入上下限+∞和0
= -e^(-∞) +e^0
顯然e^(-∞)=0,而e^0=1
所以
∫(0,+∞) e^(-x)dx
= -e^(-∞) +e^0
= 1
擴充套件資料:
分部積分:
(uv)"=u"v+uv"
得:u"v=(uv)"-uv"
兩邊積分得:∫ u"v dx=∫ (uv)" dx - ∫ uv" dx
即:∫ u"v dx = uv - ∫ uv" d,這就是分部積分公式
也可簡寫為:∫ v du = uv - ∫ u dv
常用積分公式:
1)∫0dx=c
2)∫x^udx=(x^(u+1))/(u+1)+c
3)∫1/xdx=ln|x|+c
4)∫a^xdx=(a^x)/lna+c
5)∫e^xdx=e^x+c
6)∫sinxdx=-cosx+c
7)∫cosxdx=sinx+c
8)∫1/(cosx)^2dx=tanx+c
9)∫1/(sinx)^2dx=-cotx+c
10)∫1/√(1-x^2) dx=arcsinx+c